Calvyn en die Natuurwetenskappe (Tydskrif vir Christelike Wetenskap | Journal for Christian Scholarship, 2010)
Calvin called for active labour in creation, both practical and intellectual, including the investigation of the motion of stars, determination of their assigned stations, measurement of their intervals, notation of their properties. Calvin accepts both the general revelation of God, as revealed by Holy Scripture, as well as the revelation in ‘nature’. Although his Institutes does not actually draw from the revelation of God in ‘nature’, his main theme of knowledge of God and knowledge of ourselves come to the fore in this article, covering the development of scientific principles and related world views from Plato and Aristotle through the Reformation to current natural sciences. The Biblical God created the universe ex nihilo and hence has absolute control over it. God guides history by posing man tasks. Through history of natural sciences, among other things, God fulfils His plan on earth. From the principle that the cosmonomic order is binding for all creation, the existence of a natural law was accepted. The conviction that natural laws can be stated in precise mathematical formulas gave modern science its developmental strength. Eventually the physical universe became a machine, operated by fixed, inexorable laws, repudiating God’s control over His creation. Natural sciences of the 20th century open up avenues again for God’s providence in nature while evolutionary science rejected God, but created a spiritual longing to the sacred.